Medical Data Analysis of Lumbar Disc Herniation Patients after Traditional Chinese Medicine Rehabilitation Intervention Lumbar Function Recovery - Liu Yan; Wang Chenni; Liu Fang; null LiyueYang (Applied Bionics and Biomechanics)
In order to study the efficacy of TCM rehabilitation for lumbar disc herniation, it is suggested to compare the effects of hot compress, ordinary sandbag, or hot compress with traditional Chinese medicine. A total of 79 patients with Qi stagnation and blood stasis syndrome in a traditional Chinese medicine hospital who met the diagnostic criteria of LDH and the syndrome classification in the diagnostic efficacy criteria of traditional Chinese medicine were selected. The subjects were randomly divided into groups A, B, and C: group A (26 cases) was the sandbag hot compress dry pregroup and received the simple sandbag hot compress scheme; group B (26 cases) was a simple traditional Chinese medicine hot compress intervention group, which received traditional Chinese medicine hot compress scheme; group C (27 cases) was the intervention group of traditional Chinese medicine sandbag combined with hot compress and received the scheme of traditional Chinese medicine sandbag combined with hot compress. In addition to the different hot compress media used, other aspects remained the same among the three groups. The treatment time of each hot compress was 40 min, twice a day for 2 weeks. A total of 14 cases fell out during the intervention process, and 65 subjects completed the intervention process. The experiment showed that there was no significant difference among the three groups (P>0.05). The test results were confirmed.